Materialism and Life Satisfaction: The Role of Stress and Religiosity. Issue 3 (4th October 2013) - BAKER, ANDREW M.; MOSCHIS, GEORGE P.; ONG, FON SIM; PATTANAPANYASAT, RA‐PEE
<x xml:space="preserve">Abstract</x> Materialism has been a topic of interest to consumer researchers for decades. This article explores the effect of materialism on individuals' life satisfaction using a large sample from Malaysia, a country with cultural diversity within a collectivist mainstream culture. The results suggest that the effects of materialism on life satisfaction could be indirect, mediated by stress and moderated by religiosity. The study helps to explain the mechanisms that account for the negative relationship between materialism and life satisfaction reported in previous studies conducted in many countries; it provides a blueprint and directions for further research.